Laparoscopic management for spontaneous jejunal perforation caused by nonspecific ulcer: A case report. (2017) - Sakaguchi, Tatsuma; Tokuhara, Katsuji; Nakatani, Kazuyoshi; Kon, Masanori
Highlights: Reported case of perforated jejunal nonspecific ulcer is limited. Emergency laparoscopic surgery had diagnostic and therapeutic advantages. Surgeons should be aware of it as one of the causes of small bowel perforation. Abstract: Introduction: Nonspecific small bowel ulcers are rare and there have been limited reports. We applied laparoscopic surgery successfully for the perforation caused by this disease of jejunum. Presentation of case: A 70-year-old man visited to our hospital with complaint of abdominal pain and fever. He was diagnosed abdominal peritonitis with findings of intraperitoneal gas and fluid. Emergency laparoscopic surgery was performed. A perforation 5 mm in diameter was recognized in jejunum opposite side of mesentery. Partial resection of jejunum with end-to-end anastomosis and peritoneal lavage were performed. Pathologically, an ulcer was recognized around the blowout perforation without specific inflammation. He was discharged uneventfully 12 days after surgery. Conclusion: Laparoscopic surgery has diagnostic and therapeutic advantages because of its lower invasion with a good operation view, and in case of the small bowel, it is easy to shift extra-corporeal maneuver.